2005
DOI: 10.1038/sj.jhh.1001865
|View full text |Cite
|
Sign up to set email alerts
|

Home blood-pressure monitoring among hypertensive patients in an Asian population

Abstract: Hypertension is a principal cause of mortality and morbidity in Singapore. The use of home blood-pressure monitoring (HBPM) to assess hypertensive control with digital devices in the local multi-racial population is unknown. The study determined the factors associated with hypertensive patients' use of HBPM in primary care in a multi-racial Asian population. Randomized crosssectional questionnaire survey of hypertensive patients managed in a district polyclinic. A model predicting use of HBPM was constructed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
38
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 14 publications
6
38
2
2
Order By: Relevance
“…In previous studies, compared to patients who had not taken home BP measurements, patients who had taken home BP measurements were younger, more often male and had a higher educational level or higher socioeconomic status. 15,21 Taking home BP measurements might not be associated with socioeconomic status in Japan, since the socioeconomic status of the present population is essentially equivalent. Furthermore, in the present study, patients with a family history of hypertension were more likely to take home BP measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, compared to patients who had not taken home BP measurements, patients who had taken home BP measurements were younger, more often male and had a higher educational level or higher socioeconomic status. 15,21 Taking home BP measurements might not be associated with socioeconomic status in Japan, since the socioeconomic status of the present population is essentially equivalent. Furthermore, in the present study, patients with a family history of hypertension were more likely to take home BP measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In several countries, the prevalence of patients who had taken home BP measurements among hypertensive patients has been reported to range from 19.7 to 87.3%. 15,[21][22][23][24] In Japan, approximately 30 million home BP measuring devices have been distributed. 19 Additionally, both in the guidelines for self-measurement of BP at home 18 and in the Japanese Society of Hypertension Guidelines for the Management of Hypertension, 7 the Japanese Society of Hypertension strongly recommended that patients measure their own BP at home.…”
Section: Discussionmentioning
confidence: 99%
“…A study designed at assessing the factors associated with HBP measurement in a multiracial Asian population of hypertensive patients in a primary care setting revealed 61.7% of the sample (175 patients randomly selected from 1943 patients) was aware of HBP, but only 24% used this procedure. 16 Failure to recognize benefits, lack of HBP awareness and perception of inaccuracy were, in ranking order, the most common barriers for HBP use.…”
Section: Hbp Monitoring In Clinical Practicementioning
confidence: 99%
“…We categorized all the patients who either performed self-measurements or had their BP measured at home by relatives or pharmacists as one group, since it has been shown that the lower level of home-in comparison to clinic BP-seems to be exclusively attributed to the effect of different setting (outside the hospital), rather than to the person who is taking measurements. 6 The majority of the patients used aneroid devices (in contrast to the cohort in Singapore study 5 ), since these are considerably cheaper than electronic ones, in spite of the greater difficulty in their use.…”
mentioning
confidence: 99%